Stabilność parametrów modelu ekonometrycznego a dokładność prognoz - Łapińska-Sobczak, Nina; Zatoń, Wojciech (Parameter Stability of the Econometric Model and the Forecast Accuracy, 2006)
After estimation econometric models are used for forecasting. The usual assumption is that the parameters are constant in the period of forecast. However, if the structural change (rapid or slow movement in a mechanism described by the model) takes place the reasonable approach is to vary parameters in the forecast. Here, we consider the problem of instability of the parameters in the econometric models. We apply tests based on the recursive residuals and recursive coefficients to detect model instability. We also examine trends in the parameters through the estimation sample in the long as well in the short (latest estimates in the recursive estimation) run. Then we apply constant and varying (according to the best trend line) parameters to make forecast on the econometric model. We calculate forecast errors to compare the results. The data used are quarterly and annual series for the Polish economy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 81-91